Electrostatic charge image developing toner, electrostatic charge image developer and toner cartridge

By using electrostatic charge image development toner with discontinuous phases of the adhesive resin core and coating in the image forming apparatus, the deformation and fusion problems caused by the toner due to mechanical load are solved, and the durability of the image is improved and fixing quality.

CN111752116BActive Publication Date: 2025-01-07FUJIFILM BUSINESS INNOVATION CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN201910865520.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-03-26
Filing Date
2019-09-12
Publication Date
2025-01-07
Estimated Expiration
2039-09-12

AI Technical Summary

Technical Problem

In an image forming device, the toner is deformed or fused due to mechanical load, resulting in white spots in the image, and the prior art is difficult to effectively solve this problem.

Method used

Using an electrostatic charge image development toner, the toner comprises a continuous phase and a discontinuous phase, wherein the discontinuous phase has a core and a coating of a binder resin and is dispersed in the continuous phase, with excellent loading Durability.

Benefits of technology

Through this structure, the durability of the toner to mechanical load is significantly improved, the appearance of white spots in the image is reduced, and the fixing intensity and scratch resistance of the image are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111752116B_ABST
    Figure CN111752116B_ABST
Patent Text Reader

Abstract

An electrostatic charge image developing toner, an electrostatic charge image developer, and a toner cartridge. An electrostatic charge image developing toner comprises: a continuous phase comprising a binder resin (i); and a discontinuous phase having a core comprising a binder resin (ii) and a coating covering the core and comprising a binder resin (iii), and dispersed in the continuous phase.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electrostatic charge image developing toner, an electrostatic charge image developer and a toner cartridge. Background Art

[0002] In the image forming apparatus, a toner image formed on the surface of an image holding member is transferred to the surface of a recording medium and then fixed on the recording medium by a fixing member heated and pressed in contact with the toner image to form an image.

[0003] As a toner used for such an image forming apparatus, for example, JP-A-2014-006339 discloses "a toner comprising a polyester resin A, a polyester resin B, and a colorant, wherein (1) the polyester resin A is a resin having a site capable of forming a crystal structure, (2) the polyester resin B is a resin having no site capable of forming a crystal structure, the toner has a domain derived from the polyester resin A in a cross section of the toner when the cross-sectional area of ​​the toner is observed using a transmission electron microscope (TEM), and in the domain, the maximum domain long diameter is 3.0 μm or more, (4) the average aspect ratio (long diameter / short diameter) of the domain is 4.0 to 20.0, and (5) the melting point Ta of the polyester resin A and the softening point Tb of the polyester resin B satisfy the expression "Ta <Tb”。

[0004] In addition, JP-A-2018-010286 discloses "a toner having toner particles, the toner particles containing a binder resin, a colorant, an amorphous polyester, and a crystalline polyester, wherein the binder resin contains a vinyl resin, the amorphous polyester contains a monomer unit derived from a linear aliphatic dicarboxylic acid having 6 to 12 carbon atoms and a monomer unit derived from a diol, the content of the monomer unit derived from a linear aliphatic dicarboxylic acid having 6 to 12 carbon atoms is 10 mol % to 50 mol % based on all monomer units derived from carboxylic acids of the amorphous polyester, and in a cross section of the toner particles observed with a transmission electron microscope, the vinyl resin constitutes a matrix, the amorphous polyester constitutes a domain, and the crystalline polyester is present within the domain".

[0005] In addition, JP-A-2016-114782 discloses "a toner having a structure including a binder resin, the binder resin containing a polymer having a structural unit represented by a specific structural formula, wherein the optical purity X(%)=|X(L type)-X(D type)|[here, X(L type) represents the L ratio (mol %) of the monomer component, and X(D type) represents the D ratio (mol %) of the monomer component] is 80% or less, and with respect to the monomer component represented by the structural formula, there is a structural domain in the matrix, and there is a small structural domain in the structural domain".

[0006] In addition, JP-A-2017-198980 discloses “a toner having toner particles containing a binder resin, a colorant, a releasing agent, and a crystalline polyester, wherein in cross-sectional observation of the toner particles by a transmission electron microscope, the ratio of the toner particles in which domains of the crystalline polyester and domains of the releasing agent are observed in one particle is 70% in number or more, the arithmetic mean of the maximum diameters of the domains of the releasing agent is 1.0 μm to 4.0 μm, and in a particle group consisting of the domains of the crystalline polyester and the toner particles in which the domains of the releasing agent are observed in one particle, the following conditions are satisfied: (i) the average coverage of the domains of the crystalline polyester with respect to the domains of the releasing agent is 80% or more, (ii) the average ratio of the area occupied by the domains of the crystalline polyester is 10.0% to 40.0% relative to the cross-sectional area of ​​the toner particles, and (iii) the average ratio of the area occupied by the domains of the releasing agent is 10.0% to 40.0% relative to the cross-sectional area of ​​the toner particles”. Summary of the invention

[0007] In an image forming apparatus, a mechanical load is applied to the toner at various locations (e.g., agitation for charging applied to the toner by a developing unit). Then, since the toner is deformed or fused due to the load, white spots may appear in the image. Therefore, the toner needs to have durability against the load.

[0008] Aspects of certain non-limiting embodiments of the present disclosure relate to an electrostatic charge image developing toner having excellent durability against load, compared to a case where the toner does not have a configuration in which a discontinuous phase containing a binder resin is dispersed in a continuous phase containing a binder resin (i.e., a case in which the binder resin does not constitute both the continuous phase and the discontinuous phase).

[0009] The above object is achieved by the following means.

[0010] <1>

[0011] According to one aspect of the present disclosure, there is provided an electrostatic charge image developing colorant, which includes: a continuous phase, which contains a binder resin (i); and a discontinuous phase, which has a core containing a binder resin (ii) and a coating layer covering the core and containing a binder resin (iii), and is dispersed in the continuous phase.

[0012] <2>

[0013] according to <1> An electrostatic charge image developing toner, wherein, in a cross section of the toner, a ratio of an area occupied by the discontinuous phase to a cross-sectional area of ​​the toner is 5% to 15%.

[0014] <3>

[0015] according to <1> An electrostatic charge image developing toner, wherein the discontinuous phase has an average equivalent circle diameter of 100 nm to 300 nm.

[0016] <4>

[0017] according to <1> An electrostatic charge image developing toner, wherein the coating layer has an average thickness of 25 nm to 50 nm.

[0018] <5>

[0019] according to <1> An electrostatic charge image developing toner, wherein a ratio L2 / L1 of an average thickness L2 of the coating layer to an average equivalent circle diameter L1 of the discontinuous phase is 0.12 to 0.25.

[0020] <6>

[0021] according to <1> An electrostatic charge image developing toner, wherein the binder resin (iii) contained in the coating layer has a structure different from a constituent unit in a polymer chain relative to the binder resin (i) contained in the continuous phase and the binder resin (ii) contained in the core.

[0022] <7>

[0023] according to <1> An electrostatic charge image developing toner, wherein the binder resin (iii) contained in the coating layer forms a chemical bond at an interface between the core and the coating layer with respect to the binder resin (ii) contained in the core.

[0024] <8>

[0025] according to <1> An electrostatic charge image developing toner, wherein the continuous phase contains an amorphous polyester resin A1 and a crystalline polyester resin C as a binder resin (i), the core contains an amorphous polyester resin A2 as a binder resin (ii), and the coating layer contains a vinyl resin B as a binder resin (iii).

[0026] <9>

[0027] according to <8> An electrostatic charge image developing toner, wherein a weight ratio C / A1 of the crystalline polyester resin C contained in the continuous phase to the amorphous polyester resin A1 contained in the continuous phase is 0.12 to 0.40.

[0028] <10>

[0029] according to <8> An electrostatic charge image developing toner, wherein the difference between the SP values ​​of the amorphous polyester resin A1 and the amorphous polyester resin A2 is 0.20 or less.

[0030] <11>

[0031] according to <8> An electrostatic charge image developing toner, wherein the amorphous polyester resin A1 and the amorphous polyester resin A2 both have a total of 50 wt % or more of at least one of a structure derived from a bisphenol A propylene oxide adduct and a structure derived from a bisphenol A ethylene oxide adduct.

[0032] <12>

[0033] according to <1> An electrostatic charge image developing colorant, wherein, in a cross section of the toner, when a boundary line having the same shape as that of the cross section of the toner and enclosing an area of ​​50% of the cross-sectional area of ​​the toner is coaxially drawn on the cross section of the toner, a ratio a1 / a2 of an area a1 of a discontinuous phase existing within the boundary line to an area a2 of the discontinuous phase existing outside the boundary line is 0.8 to 1.2.

[0034] <13>

[0035] According to another aspect of the present disclosure, there is provided a method comprising: <1> The electrostatic charge image developing toner is an electrostatic charge image developer.

[0036] <14>

[0037] According to another aspect of the present disclosure, a toner cartridge is provided, which is configured to accommodate <1> An electrostatic charge image developing toner, wherein the toner cartridge is detachable from the image forming apparatus.

[0038] According to <1> , <6> or <8> The invention described in provides an electrostatic charge image developing colorant having excellent durability against load as compared to a case where there is no configuration in which a discontinuous phase containing a binder resin is dispersed in a continuous phase containing a binder resin (i.e., a case where the binder resin does not constitute both the continuous phase and the discontinuous phase).

[0039] according to <2> The invention described in provides an electrostatic charge image developing toner having excellent durability against load compared with the case where the ratio of the area occupied by the discontinuous phase to the cross-sectional area of ​​the toner is less than 5%.

[0040] according to <3> The invention described in provides an electrostatic charge image developing toner having excellent durability against load compared with the case where the discontinuous phase has an average equivalent circle diameter of more than 300 nm.

[0041] according to <4> The invention described in provides an electrostatic charge image developing toner having excellent durability against load as compared with the case where the coating layer has an average thickness of less than 25 nm.

[0042] according to <5> The invention described in provides an electrostatic charge image developing toner having excellent durability against load as compared with the case where the ratio L2 / L1 of the average thickness L2 of the coating layer to the average equivalent circle diameter L1 of the discontinuous phase is less than 0.12.

[0043] according to <7> The invention described in provides an electrostatic charge image developing toner having excellent durability against load compared to a case where a binder resin (iii) contained in a coating layer does not form a chemical bond with respect to a binder resin (ii) contained in a core at an interface between a core and a coating layer.

[0044] according to <9> The invention described in provides an electrostatic charge image developing toner having excellent low-temperature fixability compared with the case where the weight ratio C / A1 of the crystalline polyester resin C contained in the continuous phase to the amorphous polyester resin A1 contained in the continuous phase is less than 0.12.

[0045] according to <10> The invention described in provides an electrostatic charge image developing toner having high image fixing strength compared with the case where the difference between the SP values ​​of the amorphous polyester resin A1 contained in the continuous phase and the amorphous polyester resin A2 contained in the core is greater than 0.20.

[0046] according to <11> The invention described in provides an electrostatic charge image developing toner having high image fixing strength compared with the case where the total amount of a structure derived from a bisphenol A propylene oxide adduct and a structure derived from a bisphenol A ethylene oxide adduct in at least one of an amorphous polyester resin A1 contained in a continuous phase and an amorphous polyester resin A2 contained in a core is less than 50% by weight.

[0047] according to <12> The invention described in provides an electrostatic charge image developing colorant having excellent durability against load compared to a case where, when a boundary line having the same shape as that of the cross section of the toner and surrounding an area of ​​50% of the cross-sectional area of ​​the toner is coaxially drawn on the cross section of the toner, the ratio a1 / a2 of the area a1 of the discontinuous phase present within the boundary line to the area a2 of the discontinuous phase present outside the boundary line is less than 0.8 and greater than 1.2.

[0048] according to <13> or <14> The invention described in provides an electrostatic charge image developer and a toner cartridge that suppress white spots in an image compared to a case where an electrostatic charge image developing toner having no configuration in which a discontinuous phase containing a binder resin is dispersed in a continuous phase containing a binder resin (i.e., the binder resin does not constitute both the continuous phase and the discontinuous phase) is applied. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Exemplary embodiments of the present invention will be described in detail based on the following drawings, in which:

[0050] Figure 1 is a cross-sectional image of an example of a toner according to an exemplary embodiment;

[0051] Figure 2 is a configuration diagram showing an example of an image forming apparatus according to an exemplary embodiment; and

[0052] Figure 3 is a configuration diagram illustrating an example of a process cartridge according to the exemplary embodiment. DETAILED DESCRIPTION

[0053] Hereinafter, exemplary embodiments of the present invention will be described.

[0054] Electrostatic image developing toner

[0055] The electrostatic charge image developing toner (hereinafter referred to as "toner") according to the exemplary embodiment includes at least one binder resin. The toner includes a continuous phase containing the binder resin and a discontinuous phase dispersed in the continuous phase, and the discontinuous phase has a core containing the binder resin and a coating layer covering the core and containing the binder resin.

[0056] The toner according to the exemplary embodiment has the above-described configuration and is therefore excellent in durability against load. The reason is presumed to be as follows.

[0057] In an image forming apparatus, a mechanical load is applied to the toner at various points. For example, in a developing unit that charges the toner by stirring, a load is applied to the toner during stirring. When the imaging speed (so-called process speed) of the machine is high, the mechanical load applied to the toner tends to increase. Then, in the case of a toner that is deformed or fused by the application of the load, white spots in the image (image defects that produce white spots on the image portion formed on the recording medium) caused by the deformation or fusion of the toner may be generated. Therefore, the toner needs to have durability against the load.

[0058] In contrast, the toner according to the exemplary embodiment has a structure in which a discontinuous phase in which a core containing a binder resin is covered with a coating layer containing a binder resin is dispersed in a continuous phase containing a binder resin.

[0059] Here, the structure of the toner according to the exemplary embodiment will be described with reference to examples. Figure 1 is a cross-sectional image of an example of a toner according to the exemplary embodiment. Figure 1 The toner shown includes a continuous phase 40 containing a binder resin and a discontinuous phase 50 dispersed in the continuous phase 40, and the discontinuous phase 50 has a core 52 containing a binder resin and a coating layer 54 covering the core 52 and containing a binder resin. That is, there is provided a structure in which the continuous phase 40 corresponding to the sea and the discontinuous phase 50 corresponding to the island form a so-called sea-island structure, and the discontinuous phase 50 corresponding to the island includes the core 52 and the coating layer 54 surrounding the core. Figure 1 The toner shown contains a release agent 60 .

[0060] Therefore, the discontinuous phase in the toner functions as a filler, and the hardness of the toner itself increases to improve durability against load compared to the case where the discontinuous phase does not exist (ie, the binder resin does not form both the continuous phase and the discontinuous phase).

[0061] Binder resins contained in the continuous phase, core and coating

[0062] The toner according to the exemplary embodiment contains at least a binder resin in the core and the coating layer forming a discontinuous phase and a binder resin in the continuous phase. Note that in the following description, the binder resin contained in the continuous phase is referred to as "(i)", the binder resin contained in the core is referred to as "(ii)", and the binder resin contained in the coating layer is referred to as "(iii)".

[0063] The binder resin (i) contained in the continuous phase, the binder resin (ii) contained in the core, and the binder resin (iii) contained in the coating layer may be the same as or different from each other. Here, examples of "resins different from each other" include resins having a structure different from the constituent units in the polymer chain (for example, synthesized using monomers having a molecular structure different from that of the raw materials of the resin) and resins having the same structure as the constituent units in the polymer chain but different in average molecular weight.

[0064] Binder resin (i) contained in the continuous phase

[0065] The continuous phase preferably contains an amorphous resin and a crystalline resin as the binder resin (i). When a crystalline resin is contained in the continuous phase, low-temperature fixability can be enhanced. Note that, from the perspective of improving low-temperature fixability, it is more preferred that the continuous phase contains an amorphous polyester resin and a crystalline polyester resin (here, in the following description, the amorphous polyester resin contained in the continuous phase is referred to as "A1", and the crystalline polyester resin contained in the continuous phase is referred to as "C").

[0066] The weight ratio of the crystalline resin to the amorphous resin contained in the continuous phase (more preferably, the weight ratio of the crystalline polyester resin C to the amorphous polyester resin A1 (C / A1)) is preferably 0.12 to 0.40, more preferably 0.15 to 0.35, and still more preferably 0.20 to 0.30.

[0067] When the weight ratio of the crystalline resin to the amorphous resin (more preferably, the weight ratio of the crystalline polyester resin C to the amorphous polyester resin A1 (C / A1)) is 0.12 or more, the low-temperature fixing property can be enhanced; on the other hand, when the weight ratio is 0.40 or less, the fixing strength of the image (especially the anti-scratch strength of the fixed image) can be enhanced, and the anti-thermal offset property can be enhanced.

[0068] Furthermore, one or more amorphous resins and crystalline resins contained in a continuous phase may be used. Furthermore, one or more amorphous polyester resins A1 and crystalline polyester resins C contained in a continuous phase may be used.

[0069] The total content of the amorphous polyester resin A1 and the crystalline polyester resin C in the entire binder resin contained in the continuous phase is preferably 50% by weight or more, more preferably 80% by weight or more, and still more preferably 100% by weight.

[0070] Binder resin (ii) contained in the core

[0071] The core preferably contains an amorphous resin (more preferably an amorphous polyester resin) as the binder resin (ii). When the amorphous resin (more preferably an amorphous polyester resin) is contained in the core, durability against load can be enhanced.

[0072] In addition, as described below, in the case where the glass transition temperature Tg of the binder resin (iii) contained in the coating layer is lower than the fixing temperature, it is more preferable to contain an amorphous resin (more preferably an amorphous polyester resin) in the core. Since the amorphous resin in the core melts out from the discontinuous phase during fixing, the fixing strength of the image (particularly the anti-scratch strength of the fixed image) can be enhanced, and the low-temperature fixing property can be enhanced. Here, in the following description, the amorphous polyester resin contained in the core is referred to as "A2".

[0073] Furthermore, one or more amorphous resins (more preferably amorphous polyester resin A2) contained in the core may be used.

[0074] The content of the amorphous polyester resin A2 in the entire binder resin contained in the core is preferably 50% by weight or more, more preferably 80% by weight or more, and still more preferably 100% by weight.

[0075] Binder resin (iii) contained in the coating layer

[0076] The binder resin (iii) contained in the coating layer is preferably a binder resin having a different structure from the constituent units in the polymer chain relative to the binder resin (i) contained in the continuous phase and the binder resin (ii) contained in the core. When the binder resin (iii) contained in the coating layer has a different structure from the constituent units in the polymer chain relative to the binder resins contained in the continuous phase and the core, the structure of the toner according to the exemplary embodiment, that is, a structure having a continuous phase and a discontinuous phase including a core and a coating layer covering the core (so-called sea-island structure) can be formed.

[0077] In addition, the binder resin (iii) contained in the coating preferably forms a chemical bond at the interface between the core and the coating relative to the binder resin (ii) contained in the core. When the binder resin forms a chemical bond, the strength at the interface between the core and the coating is enhanced, and the durability to the load can be enhanced. In addition, the structure of the toner according to the exemplary embodiment can be formed, that is, a structure having a continuous phase and a discontinuous phase containing a core and a coating covering the core (so-called sea island structure).

[0078] As described above, the binder resin (iii) contained in the coating layer is preferably a binder resin having a structure different from the constituent units in the polymer chain relative to the binder resin (i) and the binder resin (ii), and preferably forms a chemical bond at the interface between the core and the coating layer relative to the binder resin (ii). In addition, from the perspective of being able to form the structure of the toner according to the exemplary embodiment, that is, a structure having a continuous phase and a discontinuous phase including a core and a coating layer covering the core (so-called sea island structure), the binder resin (iii) contained in the coating layer preferably has low compatibility with the binder resin (i) and the binder resin (ii).

[0079] From this perspective, in the case where the continuous phase contains amorphous polyester resin A1 and crystalline polyester resin C, and the core contains amorphous polyester resin A2, the coating layer preferably contains a vinyl resin (here, in the following description, the vinyl resin contained in the coating layer is referred to as "B").

[0080] The binder resin (iii) (more preferably the vinyl resin B) contained in the coating layer preferably has a glass transition temperature Tg lower than the fixing temperature (i.e., the set temperature at the time of fixing in the image forming apparatus). When the glass transition temperature Tg of the binder resin (iii) (more preferably the vinyl resin B) is lower than the fixing temperature, the amorphous resin in the core is likely to melt out from the discontinuous phase at the time of fixing, so that the fixing strength of the image (particularly the anti-scratch strength of the fixed image) can be enhanced, and the anti-hot offset property can be enhanced.

[0081] The glass transition temperature Tg of the binder resin (iii) contained in the coating layer is preferably 40° C. or lower, more preferably 30° C. or lower, and still more preferably 20° C. or lower from the viewpoint of improving the fixing strength and low-temperature fixing property of the image.

[0082] On the other hand, from the viewpoint of enhancing the strength of the coating layer and enhancing the durability of the toner to load, the glass transition temperature Tg of the binder resin (iii) is preferably -70°C or higher, more preferably -50°C or higher, and still more preferably -40°C or higher.

[0083] The glass transition temperature Tg of the binder resin (iii) is obtained from a DSC curve obtained by differential scanning calorimetry (DSC). More specifically, the glass transition temperature is obtained according to the "extrapolated glass transition start temperature" described in the method for obtaining the glass transition temperature in JIS K 7121-1987 "Testing methods for transition temperature of plastics".

[0084] Furthermore, one or more binder resins (more preferably vinyl resin B) contained in the coating layer may be used.

[0085] The content of the vinyl resin B in the entire binder resin contained in the coating layer is preferably 50% by weight or more, more preferably 80% by weight or more, and still more preferably 100% by weight.

[0086] The relationship between the binder resin (i) contained in the continuous phase and the binder resin (ii) contained in the core

[0087] In the case where the continuous phase contains an amorphous resin (more preferably an amorphous polyester resin A1) as the binder resin (i) and the core contains an amorphous resin (more preferably an amorphous polyester resin A2) as the binder resin (ii), the amorphous resins (more preferably amorphous polyester resins A1 and A2) contained in the continuous phase and the core may be the same as or different from each other.

[0088] When the glass transition temperature Tg of the binder resin (iii) (more preferably the vinyl resin B) contained in the coating layer is lower than the fixing temperature, the compatibility between the amorphous resin (more preferably the amorphous polyester resin A1) contained in the continuous phase and the amorphous resin (more preferably the amorphous polyester resin A2) contained in the core is preferably high. Due to the high compatibility between the amorphous resins, the amorphous resin in the core melts out from the discontinuous phase during fixing and is compatible with the amorphous resin in the continuous phase, so that the fixing strength of the image (particularly the strength of the fixed image against scratching) can be enhanced, and the hot offset resistance can be enhanced.

[0089] Here, as an index of compatibility, the difference in SP value between the amorphous resin contained in the continuous phase and the amorphous resin contained in the core (more preferably the amorphous polyester resin A1 and the amorphous polyester resin A2) is preferably 0.20 or less, and more preferably 0.15 or less.

[0090] Here, in the exemplary embodiment, the SP value (unit: (cal / cm 3 ) 1 / 2 ) is calculated by the Fedor method. Specifically, the SP value is calculated by the following equation.

[0091] SP value = √(Ev / v) = √(∑Δei / ∑Δvi)

[0092] In the equation, Ev is the evaporation energy (cal / mol) and v is the molar volume (cm 3 / mol), Δei represents the evaporation energy of each atom or atomic group, and Δvi represents the molar volume of each atom or atomic group.

[0093] The details of this calculation method are described in "Polymer Engineering and Science" (Vol. 14, p. 147 (1974), Junji Mukai et al. (1981)), "Practical Polymers for Engineers" (Kodansha, p. 66), "Polymer Handbook" (4th edition, published by Wiley Interscience), etc., and the same method is applied to the exemplary embodiment. In the exemplary embodiment, (cal / cm 3 ) 1 / 2 as the unit of the SP value, but according to practice, the unit is omitted and described as without dimension.

[0094] Furthermore, from the viewpoint of enhancing compatibility, the amorphous polyester resin A1 contained in the continuous phase and the amorphous polyester resin A2 contained in the core are preferably resins having a total amount of 50 wt % or more, more preferably 60 wt % or more, and still more preferably 70 wt % or more of at least one of a structure derived from a bisphenol A propylene oxide adduct and a structure derived from a bisphenol A ethylene oxide adduct.

[0095] Note that, in the amorphous polyester resins A1 and A2, the upper limit value of the total amount of the structure derived from the bisphenol A propylene oxide adduct and the structure derived from the bisphenol A ethylene oxide adduct is not particularly limited as long as it is within the range that can constitute the polyester resin. That is, if the amorphous polyester resins A1 and A2 are polycondensates of a polyvalent carboxylic acid and a polyvalent alcohol, there is no particular limitation as long as it is within the ratio range of the polyvalent carboxylic acid and the polyvalent alcohol that can constitute the polyester resin.

[0096] Note that, in the amorphous polyester resins A1 and A2, the total amount of the structure derived from the bisphenol A propylene oxide adduct and the structure derived from the bisphenol A ethylene oxide adduct can be obtained by analysis using NMR.

[0097] From the viewpoint of enhancing compatibility, the amorphous resin contained in the continuous phase and the amorphous resin contained in the core (more preferably amorphous polyester resin A1 and amorphous polyester resin A2) are preferably resins having only constituent units having the same structure as constituent units in the polymer chain (for example, they are synthesized using only monomers having the same molecular structure as the raw materials of the resin).

[0098] Furthermore, analysis of the constituent units of the resin in the polymer chain can be performed by NMR.

[0099] Properties of the discontinuous phase

[0100] When observing the cross section of the toner, the ratio of the area occupied by the discontinuous phase to the cross-sectional area of ​​the toner is preferably 5% to 15%, more preferably 6% to 14%, and still more preferably 7% to 12%.

[0101] When the ratio of the area occupied by the discontinuous phase is 5% or more, there is a large amount of the discontinuous phase that exhibits a filler function, and the durability of the toner against load can be enhanced. In addition, in the case where the glass transition temperature Tg of the binder resin (iii) contained in the coating layer is lower than the fixing temperature, and the core contains an amorphous resin (more preferably an amorphous polyester resin A2), the amount of the amorphous resin melted out from the core during fixing increases, so that the fixing strength of the image (particularly the anti-scratch strength of the fixed image) can be enhanced, and the hot offset resistance can be enhanced.

[0102] On the other hand, when the ratio of the area occupied by the discontinuous phase is 15% or less, a flexible toner is easily obtained because there is not an excessive amount of the discontinuous phase. In the case where the continuous phase contains an amorphous resin and a crystalline resin (more preferably an amorphous polyester resin A1 and a crystalline polyester resin C), low-temperature fixability can be enhanced because there is not an excessively small amount of the continuous phase.

[0103] The average equivalent circle diameter L1 of the discontinuous phase is preferably 100 nm to 300 nm, and more preferably 120 nm to 250 nm.

[0104] When the average equivalent circle diameter of the discontinuous phase is 100 nm or more, toner manufacturability, particularly controllability of toner particle size and controllability of toner shape can be improved.

[0105] On the other hand, when the average equivalent circle diameter is 300 nm or less, the inclusion of the discontinuous phase (i.e., island) by the continuous layer (i.e., sea) can be enhanced, and the durability of the toner against load can be enhanced. Therefore, white spots in the image caused by deformation or fusion of the toner can be suppressed.

[0106] The average thickness L2 of the coating layer is preferably 25 nm to 50 nm, more preferably 30 nm to 40 nm.

[0107] When the average thickness of the coating layer is 25 nm or more, mixing of the continuous phase and the core during toner production is suppressed, so that durability of the toner against loading can be enhanced.

[0108] On the other hand, when the average thickness is 50 nm or less, the low-temperature fixability can be enhanced.

[0109] The ratio L2 / L1 of the average equivalent circle diameter L1 of the discontinuous phase to the average thickness L2 of the coating layer is preferably 0.12 to 0.25, more preferably 0.15 to 0.20.

[0110] When the ratio L2 / L1 is 0.12 or more, mixing of the continuous phase and the core during toner production is suppressed, so that durability of the toner against load can be enhanced.

[0111] On the other hand, when the ratio L2 / L1 is 0.25 or less, the low temperature fixability can be enhanced.

[0112] In the toner according to the exemplary embodiment, preferably, the discontinuous phase is uniformly dispersed throughout the toner. By dispersing the discontinuous phase with high uniformity, the non-uniformity of the function of the discontinuous phase as a filler is suppressed, so that the durability of the toner against load can be improved.

[0113] The area ratio of the discontinuous phase between the inner area and the outer area of ​​the toner in the cross section of the toner is used as an index of dispersibility. Specifically, when observing the cross section of the toner, a boundary line having the same shape as the shape of the cross section of the toner and enclosing an area of ​​50% of the cross-sectional area of ​​the toner is coaxially drawn on the cross section. That is, a boundary line having the same shape as the shape of the cross section of the toner and a smaller outline than the shape of the cross section of the toner is drawn on the cross-sectional image of the toner to divide the cross-sectional area of ​​the toner into an area within the boundary line and an area outside the boundary line in a manner of an area ratio of 1:1. The ratio m1 / m2 of the area m1 of the discontinuous phase existing within the boundary line to the area m2 of the discontinuous phase existing outside the boundary line is preferably 0.8 to 1.2, and more preferably 0.9 to 1.1.

[0114] Here, a method of measuring each property of the discontinuous phase by observing a cross section of the toner will be described.

[0115] Toner particles are embedded with bisphenol A type liquid epoxy resin and curing agent, and then cut samples are produced. Next, the cut samples are cut at -100°C using a cutter using a diamond tool (e.g., Leica ultramicrotome manufactured by Hitachi Technologies) to produce samples for observation. In addition, when it is desired to increase the brightness difference (contrast) described later, the sample for observation can be left in a dryer under a ruthenium tetroxide atmosphere for dyeing. In addition, the dyeing depends on the degree of dyeing of the tape left in the dryer.

[0116] The observation sample thus obtained was observed by a scanning transmission electron microscope (STEM). The image was recorded at a magnification at which the cross section of one toner particle fell within the field of view. For the recorded image, image analysis was performed under the condition of 0.010000 μm / pixel using image analysis software (WinRoof manufactured by Mitani Corporation). According to the image analysis, the shape of the cross section of the discontinuous phase was extracted by the brightness difference (contrast) between the binder resin of the continuous phase (sea) of the toner particle and the binder resin of the discontinuous phase (island) having a core and a coating.

[0117] Then, a projection area is obtained based on the shape of the extracted cross section of the discontinuous phase. From the projection area, the ratio of the total area of ​​the discontinuous phase to the cross-sectional area of ​​the toner is calculated for each of the 100 toners, and the arithmetic mean thereof is set as the ratio of the area occupied by the discontinuous phase to the cross-sectional area of ​​the toner.

[0118] Furthermore, the equivalent circle diameter of the discontinuous phase is obtained from the projected area. Note that the equivalent circle diameter is given by the expression “2×(projected area / π) 1 / 2” Calculation. 100 toners are observed, a discontinuous phase is selected for each toner, its equivalent circle diameter is obtained, and its arithmetic mean is set as the average equivalent circle diameter L1 of the discontinuous phase.

[0119] In addition, the shape of the cross section of the core is extracted by the brightness difference (contrast) between the binder resin of the core and the binder resin of the coating. Based on the shape of the cross section of the core, the projection area of ​​the core is obtained, and the equivalent circular diameter of the core is obtained. As in the above L1, 100 toners are observed, a core is selected for each toner, its equivalent circular diameter is obtained, and its arithmetic mean is set as the average equivalent circular diameter L3 of the core. Then, according to the difference between L1 and L3, the average thickness L2 of the coating is obtained by the expression "(L1-L3) / 2".

[0120] Furthermore, in the cross-sectional image, a boundary line having the same shape as that of the cross-sectional area of ​​the toner and surrounding an area of ​​50% of the cross-sectional area of ​​the toner is coaxially drawn on the cross-sectional area of ​​the toner. For each of the 100 toners, the ratio of the area m1 of the discontinuous phase existing within the boundary line to the area m2 of the discontinuous phase existing outside the boundary line is calculated, and the arithmetic mean thereof is set as the ratio m1 / m2.

[0121] Here, the method for forming the structure of the toner according to the exemplary embodiment (ie, the structure including the continuous phase and the discontinuous phase having the core and the coating layer) is not particularly limited. For example, as an example, the following method of the coalescence method is illustrated.

[0122] First, a resin particle dispersion of an amorphous polyester resin A2 having an unsaturated double bond is prepared. A composite resin particle dispersion having a coating layer containing a vinyl resin B around a core containing the amorphous polyester resin A2 is produced by adding a vinyl monomer and an initiator to the obtained resin particle dispersion and reacting them. Since the amorphous polyester resin A2 has an unsaturated double bond, it forms a chemical bond with the vinyl resin B at the interface between the core and the coating layer.

[0123] By using the coalescence method to produce a toner using the composite resin particle dispersion, the resin particle dispersion of the separately produced amorphous polyester resin A1, and the resin particle dispersion of the crystalline polyester resin C, a toner having a structure including a continuous phase and a discontinuous phase including a core and a coat layer is obtained.

[0124] Note that it is considered that the toner having the above-described structure is not easily obtained by using a melt kneading method in which the temperature becomes high as the resin melts or a suspension polymerization method in which the resin is dissolved in a solvent.

[0125] Furthermore, in the above-mentioned production method, the ratio of the area occupied by the discontinuous phase to the cross-sectional area of ​​the toner can be controlled by the amount of the composite resin particle dispersion added when the toner is produced. Furthermore, the average equivalent circle diameter L1 of the discontinuous phase and the average thickness L2 of the coating layer can be controlled by the particle size of the amorphous polyester resin A2 in the resin particle dispersion and the amount of the vinyl monomer added relative to the amorphous polyester resin A2.

[0126] Next, each component and the like constituting the toner according to the exemplary embodiment will be described in detail.

[0127] The toner according to the exemplary embodiment is configured to preferably include toner particles and an external additive if necessary.

[0128] Toner particles

[0129] The toner particles are configured to include a binder resin and, if necessary, a colorant, a release agent, and other additives. The toner particles include a continuous phase containing a binder resin and a discontinuous phase dispersed in the continuous phase, and the discontinuous phase has a core containing the binder resin and a coating covering the core and containing the binder resin.

[0130] Binder resin

[0131] Examples of the binder resin contained in the continuous phase, core and coating layer in the toner particles include vinyl resins formed from homopolymers of monomers such as styrene (e.g., styrene, p-chlorostyrene and α-methylstyrene), (meth)acrylates (e.g., methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, lauryl methacrylate and 2-ethylhexyl methacrylate), ethylenically unsaturated nitriles (e.g., acrylonitrile and methacrylonitrile), vinyl ethers (e.g., vinyl methyl ether and vinyl isobutyl ether), vinyl ketones (e.g., vinyl methyl ketone, vinyl ethyl ketone and vinyl isopropenyl ketone) and olefins (e.g., ethylene, propylene and butadiene), or copolymers obtained by combining two or more of these monomers.

[0132] As the binder resin, there are also exemplified non-vinyl resins such as epoxy resins, polyester resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins and modified rosins, mixtures of non-vinyl resins and vinyl resins, or graft polymers obtained by polymerizing vinyl monomers in the coexistence of these non-vinyl resins.

[0133] These binder resins may be used alone or in combination of two or more in each of the continuous phase, the core and the coating layer.

[0134] Although not particularly limited, in the toner particles according to the exemplary embodiment, preferably, the continuous phase contains the amorphous polyester resin A1 and the crystalline polyester resin C, the core contains the amorphous polyester resin A2, and the coating layer contains a vinyl resin.

[0135] Examples of the polyester resin include well-known amorphous polyester resins. As the polyester resin, a crystalline polyester resin may be used in combination with an amorphous polyester resin. Here, the content of the crystalline polyester resin may be used in a range of 2 wt % to 40 wt % (preferably 2 wt % to 20 wt %) relative to the entire binder resin in the toner.

[0136] Furthermore, the "crystallinity" of a resin means having a clear endothermic peak rather than a stepwise endothermic change in differential scanning calorimetry (DSC), and specifically means that the half width of the endothermic peak is within 10°C when measured at a heating rate of 10 (°C / min).

[0137] On the other hand, "amorphous" of a resin means that the half width exceeds 10°C, a stepwise endothermic change is shown, or no clear endothermic peak is observed.

[0138] Amorphous polyester resin

[0139] Examples of the amorphous polyester resin include polycondensates of polyvalent carboxylic acids and polyols. As the amorphous polyester resin, a commercial product may be used or a synthetic product may be used.

[0140] Examples of the polyvalent carboxylic acid include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenyl succinic acid, adipic acid, and sebacic acid), alicyclic dicarboxylic acids (e.g., cyclohexane dicarboxylic acid), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, and naphthalene dicarboxylic acid), and anhydrides thereof or lower alkyl esters thereof (having, for example, 1 to 5 carbon atoms). Among them, for example, aromatic dicarboxylic acids are preferred as the polyvalent carboxylic acid.

[0141] As the polyvalent carboxylic acid, a trivalent or higher carboxylic acid adopting a crosslinked structure or a branched structure may be used in combination with a dicarboxylic acid. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, and anhydrides thereof or lower alkyl esters thereof (having, for example, 1 to 5 carbon atoms).

[0142] The polyvalent carboxylic acids may be used alone or in combination of two or more.

[0143] Examples of the polyol include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, and neopentyl glycol), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, and hydrogenated bisphenol A), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A and propylene oxide adducts of bisphenol A). Among them, for example, aromatic diols and alicyclic diols are preferably used as the polyol, and aromatic diols are more preferably used as the polyol.

[0144] As the polyol, a trivalent or higher polyol adopting a crosslinked structure or a branched structure may be used in combination with a diol. Examples of the trivalent or higher polyol include glycerin, trimethylolpropane, and pentaerythritol.

[0145] The polyols may be used alone or in combination of two or more.

[0146] The glass transition temperature Tg of the amorphous polyester resin is preferably in the range of 50°C to 80°C, more preferably in the range of 50°C to 65°C.

[0147] The glass transition temperature is obtained from a DSC curve obtained by differential scanning calorimetry (DSC). More specifically, the glass transition temperature is obtained according to the "extrapolated glass transition start temperature" described in the method for obtaining the glass transition temperature in JIS K 7121-1987 "Testing methods for transition temperature of plastics".

[0148] The weight average molecular weight Mw of the amorphous polyester resin is preferably in the range of 5,000 to 1,000,000, more preferably in the range of 7,000 to 500,000.

[0149] The number average molecular weight Mn of the amorphous polyester resin is preferably in the range of 2,000 to 100,000.

[0150] The molecular weight distribution Mw / Mn of the amorphous polyester resin is preferably in the range of 1.5 to 100, and more preferably in the range of 2 to 60.

[0151] The weight average molecular weight and number average molecular weight were measured by gel permeation chromatography (GPC). GPC & HLC-8120GPC manufactured by TOSOH CORPORATION was used as a measuring device, and TSK gel Super HM-M (15 cm) chromatographic column and THF solvent manufactured by TOSOH CORPORATION were used to carry out the molecular weight measurement of GPC. The weight average molecular weight and number average molecular weight were calculated by using a molecular weight calibration curve drawn using a monodisperse polystyrene standard sample according to the above measurement results.

[0152] The amorphous polyester resin is produced using a known production method. Specific examples thereof include a method in which a reaction is conducted at a polymerization temperature set within a range of 180° C. to 230° C., if necessary, under reduced pressure in a reaction system while removing water or alcohol generated during condensation.

[0153] When the monomers of the raw materials are insoluble or incompatible at the reaction temperature, a high boiling point solvent may be added as a solubilizing agent to dissolve the monomers. In this case, the polycondensation reaction is carried out while the solubilizing agent is distilled off. When there are monomers with poor compatibility in the copolymerization reaction, the monomers with poor compatibility and the acid or alcohol to be polycondensed with the monomers may be condensed in advance and then polycondensed with the main component.

[0154] Crystalline polyester resin

[0155] Examples of the crystalline polyester resin include polycondensates of polyvalent carboxylic acids and polyols. Among them, as the crystalline polyester resin, a commercial product may be used or a synthetic product may be used.

[0156] Here, the crystalline polyester resin is preferably a condensate using a polymerizable monomer having a linear aliphatic group rather than a polymerizable monomer having an aromatic group in order to easily form a crystal structure.

[0157] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, and 1,18-octadecanedicarboxylic acid), aromatic dicarboxylic acids (e.g., phthalic acid, isophthalic acid, terephthalic acid, dibasic acids such as naphthalene-2,6-dicarboxylic acid), and anhydrides thereof or lower alkyl esters thereof (having, for example, 1 to 5 carbon atoms).

[0158] As the polyvalent carboxylic acid, a trivalent or higher carboxylic acid adopting a cross-linked structure or a branched structure can be used in combination with a dicarboxylic acid. Examples of the trivalent carboxylic acid include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, and 1,2,4-naphthalenetricarboxylic acid) and anhydrides thereof or lower alkyl esters thereof (having, for example, 1 to 5 carbon atoms).

[0159] As the polyvalent carboxylic acid, a dicarboxylic acid having a sulfonic acid group and a dicarboxylic acid having an olefinic double bond can be used in combination with these dicarboxylic acids. The polyvalent carboxylic acid can be used alone or in combination of two or more.

[0160] Examples of polyols include aliphatic diols (e.g., straight-chain aliphatic diols having 7 to 20 carbon atoms in the main chain portion). Examples of aliphatic diols include ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosanediol. Among them, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol are preferably used as aliphatic diols. As polyols, trivalent or higher-valent alcohols having a cross-linked structure or a branched structure may be used in combination with diols. Examples of trivalent or higher-valent alcohols include glycerin, trimethylolethane, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more.

[0161] Here, the polyol preferably has an aliphatic diol content of 80 mol % or more, and more preferably has an aliphatic diol content of 90 mol % or more.

[0162] The melting temperature of the crystalline polyester resin is preferably 50°C to 100°C, more preferably 55°C to 90°C, still more preferably 60°C to 85°C.

[0163] Note that the melting temperature is obtained from a DSC curve obtained by differential scanning calorimetry (DSC), and specifically, is obtained according to the “melting peak temperature” described in the method for obtaining the melting temperature in JIS K 7121-1987 “Testing methods for transition temperatures of plastics”.

[0164] The weight average molecular weight Mw of the crystalline polyester resin is preferably 6,000 to 35,000.

[0165] Similar to the amorphous polyester resin, the crystalline polyester resin is obtained, for example, by a known production method.

[0166] Vinyl resin

[0167] Vinyl resin is a polymer obtained by polymerizing at least one vinyl monomer having a vinyl group (CH2=C(-R B1 )-; Here, R B1 represents a hydrogen atom or a methyl group).

[0168] In the present specification, "(meth)acrylic acid" is an expression including "acrylic acid" and "methacrylic acid".

[0169] Examples of vinyl monomers include (meth)acrylic acid and (meth)acrylic acid esters. Examples of (meth)acrylic acid esters include alkyl (meth)acrylic acid esters (such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, n-lauryl (meth)acrylate, n-tetradecyl (meth)acrylate, n-hexadecyl (meth)acrylate, n-octadecyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, isopentyl (meth)acrylate, pentyl (meth)acrylate, neopentyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, isooctyl (meth)acrylate, 2-hydroxy-2-(meth)acrylate, 1,2-dimethyl ...

[0063] In some embodiments, the present invention relates to alkyl (meth)acrylates such as cyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, aryl (meth)acrylates such as phenyl (meth)acrylate, biphenyl (meth)acrylate, diphenylethyl (meth)acrylate, tert-butylphenyl (meth)acrylate and triphenyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, methoxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, β-carboxyethyl (meth)acrylate, (meth)acrylamide, styrene, alkyl-substituted styrenes such as α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene and 4-ethylstyrene, halogen-substituted styrenes such as 2-chlorostyrene, 3-chlorostyrene and 4-chlorostyrene and vinylnaphthalene.

[0170] Furthermore, a vinyl monomer having two or more functional groups (preferably, a polyfunctional vinyl monomer having two or more vinyl groups) is also used.

[0171] Examples of the bifunctional vinyl monomers include divinylbenzene, divinylnaphthalene, di(meth)acrylate compounds (e.g., diethylene glycol di(meth)acrylate, methylenebis(meth)acrylamide, decanediol diacrylate, and glycidyl(meth)acrylate), polyester di(meth)acrylate, and 2-([1′-methylpropyleneamino]carboxyamino)ethyl methacrylate.

[0172] Examples of trifunctional or higher vinyl monomers include tri(meth)acrylate compounds (e.g., pentaerythritol tri(meth)acrylate, trimethylolethane tri(meth)acrylate, and trimethylolpropane tri(meth)acrylate), tetra(meth)acrylate compounds (e.g., pentaerythritol tetra(meth)acrylate and oligoesters (meth)acrylate), 2,2-bis(4-methacryloyloxy, polyethoxyphenyl)propane, diallyl phthalate, triallyl cyanurate, triallyl isocyanurate, triallyl trimellitate, and diaryl chlorendic acid.

[0173] Note that as the vinyl monomer, a (meth)acrylate having an alkyl group of 2 to 14 carbon atoms (preferably 2 to 10 carbon atoms, more preferably 3 to 8 carbon atoms) is preferred from the viewpoint of fixability.

[0174] The vinyl monomers may be used alone or in combination of two or more.

[0175] In the case where a vinyl monomer is contained in the coating layer, the glass transition temperature Tg is preferably lower than the fixing temperature (ie, the set temperature at the time of fixing in the image forming apparatus).

[0176] The content of the binder resin is, for example, preferably 40% by weight to 95% by weight, more preferably 50% by weight to 90% by weight, still more preferably 60% by weight to 85% by weight, relative to the entire toner particles.

[0177] Colorants

[0178] Examples of the colorant include various types of pigments such as carbon black, chrome yellow, Hansa yellow, benzidine yellow, vat yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, Varacan orange, watch red, permanent red, brilliant carmine 3B, brilliant carmine 6B, Dupont Oil Red, pyrazolone red, lithotripter red, rhodamine B Lake, Red Lake C, pigment red, rose bengal, aniline blue, ultramarine blue, calco oil blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, and malachite green oxalate, or various types of dyes such as acridine dyes, xanthene dyes, azo dyes, benzoquinone dyes, azine dyes, anthraquinone dyes, thioindigo dyes, dioxazine dyes, thiazine dyes, azomethine dyes, indigo dyes, phthalocyanine dyes, aniline black dyes, polymethine dyes, triphenylmethane dyes, diphenylmethane dyes, and thiazole dyes.

[0179] In addition, a white pigment may be included as a colorant. Examples of white pigments include titanium oxide (such as titanium oxide particles having anatase type and titanium oxide particles having rutile type), barium sulfate, zinc oxide, and calcium carbonate. Among them, titanium oxide is preferred as a white pigment.

[0180] In addition, a bright color pigment may be included as a colorant. Examples of the bright color pigment include pearlescent pigment powder, aluminum powder, metal powder such as stainless steel powder, metal flakes, glass beads, glass flakes, mica, and mica iron oxide.

[0181] The coloring agents may be used alone or in combination of two or more.

[0182] As the colorant, a surface-treated colorant may be used, if necessary, and it may be used together with a dispersant. In addition, a plurality of colorants may be used in combination.

[0183] The content of the colorant is preferably 1% by weight to 30% by weight, more preferably 3% by weight to 15% by weight, relative to the entire toner particles.

[0184] Release agent

[0185] Examples of the release agent include hydrocarbon wax, natural wax such as carnauba wax, rice wax and candelilla wax, synthetic wax or mineral wax or petroleum wax such as montan wax, and ester wax such as fatty acid ester and montanic acid ester. However, the release agent is not limited to the above examples.

[0186] The melting temperature of the releasing agent is preferably in the range of 50°C to 110°C, and further preferably in the range of 60°C to 100°C.

[0187] Note that the melting temperature is obtained from a DSC curve obtained by differential scanning calorimetry (DSC), and specifically, is obtained according to the “melting peak temperature” described in the method for obtaining the melting temperature in JIS K 7121-1987 “Testing methods for transition temperatures of plastics”.

[0188] The content of the releasing agent is preferably from 1% by weight to 20% by weight, more preferably from 5% by weight to 15% by weight, relative to the entire toner particles.

[0189] Other additives

[0190] Examples of other additives include well-known additives such as magnetic materials, electrostatic charge control agents, and inorganic powders. These additives are contained in toner particles as internal additives.

[0191] Properties of toner particles

[0192] The toner particles may be toner particles having a single-layer structure, or toner particles having a so-called core and shell structure consisting of a core (so-called core particle) and a coating layer (so-called shell layer) coated on the core.

[0193] Here, the toner particles having a core and shell structure are preferably composed of, for example, a core containing a binder resin, and, if necessary, other additives such as a colorant and a releasing agent, and a coating layer containing a binder resin.

[0194] The volume average particle diameter D50v of the toner particles is preferably from 2 μm to 10 μm, more preferably from 4 μm to 8 μm.

[0195] Various average particle diameters and various particle diameter distribution indices of the toner particles are measured using a Coulter Counter II (manufactured by Beckman Coulter, Inc.), and the electrolyte solution is measured using ISOTON-II (manufactured by Beckman Coulter, Inc.).

[0196] In the measurement, 0.5 mg to 50 mg of the measurement sample is added as a dispersant to 2 ml of a 5 wt % aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate), and the resulting material is added to 100 ml to 150 ml of an electrolyte.

[0197] The electrolyte in which the sample was suspended was subjected to a dispersion treatment for one minute using an ultrasonic disperser, and the particle size distribution of particles having a particle size of 2 to 60 μm was measured by a Coulter Counter II using an aperture having an aperture of 100 μm. 50,000 particles were sampled.

[0198] The cumulative distribution of volume and number is plotted from the minimum diameter side with respect to the particle size range (so-called channel) separated based on the measured particle size distribution. The particle size corresponding to the cumulative percentage of 16% is defined as the particle size corresponding to the volume average particle size D16v and the number average particle size D16p, and the particle size corresponding to the cumulative percentage of 50% is defined as the particle size corresponding to the volume average particle size D50v and the number average particle size D50p. In addition, the particle size corresponding to the cumulative percentage of 84% is defined as the particle size corresponding to the volume average particle size D84v and the number average particle size D84p.

[0199] Using these data, the volume particle size distribution index (GSDv) is calculated as (D84v / D16v) 1 / 2 , and the particle size distribution index (GSDp) is calculated as (D84p / D16p) 1 / 2 .

[0200] The average circularity of the toner particles is preferably from 0.94 to 1.00, more preferably from 0.95 to 0.98.

[0201] The average circularity of the toner particles is calculated by (circumference of equivalent circle) / (circumference) [(circumference of a circle having the same projected area as the particle image) / (circumference of the particle projected image)]. Specifically, the above value is measured by using the following method.

[0202] The average circularity of the toner particles was calculated by using a flow particle image analyzer (FPIA-3000 manufactured by Sysmex Co., Ltd.) which first sucks and collects the toner particles to be measured to form a flake flow, then captures the particle image as a static image by instantaneously emitting a flash, and then performs image analysis on the obtained particle image. 3500 particles were sampled when calculating the average circularity.

[0203] In the case where the toner contains an external additive, a developer containing the toner to be measured is dispersed in water containing a surfactant, and then the water is subjected to ultrasonic treatment to obtain toner particles from which the external additive is removed.

[0204] External additives

[0205] Examples of external additives include inorganic particles. Examples of inorganic particles include SiO2, TiO2, Al2O3, CuO, ZnO, SnO2, CeO2, Fe2O3, MgO, BaO, CaO, K2O, Na2O, ZrO2, CaO·SiO2, K2O·(TiO2)n, Al2O3·2SiO2, CaCO3, MgCO3, BaSO4, and MgSO4.

[0206] The surface of the inorganic particles as external additives can be subjected to hydrophobic treatment. The hydrophobic treatment is performed, for example, by immersing the inorganic particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and examples thereof include silane coupling agents, silicone oils, titanate coupling agents, and aluminum coupling agents. These hydrophobic treatment agents can be used alone or in combination of two or more.

[0207] The amount of the hydrophobizing agent is generally, for example, 1 to 10 parts by weight relative to 100 parts by weight of the inorganic particles.

[0208] Examples of the external additive include resin particles such as polystyrene, polymethyl methacrylate (PMMA), and melamine resin, detergents such as higher fatty acid metal salts represented by zinc stearate, and particles of fluorine polymers.

[0209] The content of the external additive is preferably 0.01% by weight to 5% by weight, more preferably 0.01% by weight to 2.0% by weight, relative to the entire toner particles.

[0210] Toner production method

[0211] Next, a method of producing a toner according to an exemplary embodiment will be described. The toner according to the exemplary embodiment may be obtained by adding an external additive to toner particles from the outside after the toner particles are produced.

[0212] Toner particles can be produced by using any of dry methods (eg, kneading and pulverization) and wet methods (eg, aggregation and coalescence, suspension polymerization, and dissolution suspension). The production method of the toner particles is not particularly limited, and a known method can be used.

[0213] Among them, toner particles can be obtained by using an aggregation method and a coalescence method.

[0214] Specifically, for example, in the case of producing toner particles by using an aggregation method and a coalescence method, toner particles are produced by the following steps including a step of preparing a resin particle dispersion in which resin particles constituting a binder resin are dispersed (resin particle dispersion preparation step), a step of forming aggregated particles by aggregating resin particles (and, if necessary, other particles) in the resin particle dispersion (and, if necessary, in a dispersion in which other particle dispersions are mixed) (aggregate particle formation step), and a step of preparing toner particles by heating the aggregated particle dispersion in which the aggregated particles are dispersed to aggregate the aggregated particles to form toner particles (coalescence step).

[0215] Hereinafter, each step will be described in detail.

[0216] In the following description, a method of obtaining toner particles including a colorant and a release agent will be described; however, if necessary, a colorant and a release agent may be used. Other additives other than the colorant and the release agent may also be used.

[0217] Resin particle dispersion preparation steps

[0218] First, for example, a resin particle dispersion in which resin particles corresponding to the binder resin are dispersed, a colorant particle dispersion in which colorant particles are dispersed, and a releasing agent particle dispersion in which releasing agent particles are dispersed are prepared.

[0219] Here, the resin particle dispersion is produced, for example, by dispersing the resin particles in a dispersion medium using a surfactant.

[0220] For example, an aqueous medium is used as the dispersion medium used in the resin particle dispersion.

[0221] Examples of the aqueous medium include water (such as distilled water, ion-exchanged water, etc.), alcohols, etc. The medium may be used alone or in combination of two or more.

[0222] Examples of surfactants include anionic surfactants such as sulfates, sulfonates, phosphates and soap anionic surfactants; cationic surfactants such as amine salts and quaternary ammonium salt cationic surfactants; and nonionic surfactants such as polyethylene glycol, alkylphenol ethylene oxide adducts and polyols. Among these surfactants, anionic surfactants and cationic surfactants are particularly preferably used. Nonionic surfactants can be used in combination with anionic surfactants or cationic surfactants.

[0223] The surfactants may be used alone or in combination of two or more.

[0224] In the resin particle dispersion, as a method for dispersing the resin particles in the dispersion medium, a general dispersion method by using, for example, a rotary shearing type homogenizer, a ball mill with a medium, a sand mill, or a Dyno mill is exemplified. In addition, depending on the type of the resin particles, the resin particles may be dispersed in the resin particle dispersion by using, for example, a phase inversion emulsification method.

[0225] The phase inversion emulsification method is a method of dispersing a resin in an aqueous medium in the form of particles by dissolving the resin to be dispersed in a hydrophobic organic solvent in which the resin is soluble, neutralizing by adding a base to an organic continuous phase (O phase), and performing inversion of the resin from W / O to O / W (so-called phase inversion) by adding an aqueous medium (W phase) to prepare a discontinuous phase.

[0226] The volume average particle diameter of the resin particles dispersed in the resin particle dispersion is, for example, preferably 0.01 μm to 1 μm, more preferably 0.08 μm to 0.8 μm, and still more preferably 0.1 μm to 0.6 μm. With respect to the volume average particle diameter of the resin particles, the cumulative distribution of the volume is plotted from the minimum diameter side with respect to the particle diameter range (so-called channel) separated using the particle diameter distribution obtained by measurement using a laser diffraction type particle diameter distribution measuring device (for example, manufactured by Horiba, Ltd., LA-700), and the particle diameter corresponding to the cumulative percentage of 50% with respect to the entire particles is set as the volume average particle diameter D50v. Note that the volume average particle diameter of particles in other dispersions is also measured in the same manner.

[0227] The content of the resin particles contained in the resin particle dispersion is preferably from 5% by weight to 50% by weight, and more preferably from 10% by weight to 40% by weight.

[0228] Note that the colorant particle dispersion and the release agent particle dispersion are also produced in the same manner as the resin particle dispersion. That is, the volume average particle diameter, dispersion medium, dispersion method, and particle content of the particles in the resin particle dispersion are the same as those of the colorant particles dispersed in the colorant particle dispersion and the release agent particles dispersed in the release agent particle dispersion.

[0229] In an exemplary embodiment, in the resin particle dispersion preparation step, a composite resin particle dispersion having a coating layer containing a binder resin (iii) (more preferably a vinyl resin B) around a core containing a binder resin (ii) (more preferably amorphous polyester resin A2) is preferably produced.

[0230] For example, a composite resin particle dispersion having a coating layer containing the vinyl resin B around a core containing the amorphous polyester resin A2 can be produced by preparing a resin particle dispersion of an amorphous polyester resin A2 having an unsaturated double bond, and adding a vinyl monomer and an initiator to the obtained resin particle dispersion and reacting them.

[0231] Furthermore, a resin particle dispersion for a continuous phase containing the binder resin (i) (more preferably a resin particle dispersion containing the amorphous polyester resin A1 and a resin particle dispersion containing the crystalline polyester resin C) is preferably prepared separately from the composite resin particle dispersion.

[0232] Aggregate particle formation step

[0233] Next, the resin particle dispersion, the colorant particle dispersion, and the release agent particle dispersion are mixed with each other. In addition, in the mixed dispersion, the resin particles, the colorant particles, and the release agent particles are mixed together to form aggregated particles having a diameter close to the target diameter of the toner particles and containing the resin particles, the colorant particles, and the release agent particles.

[0234] In the exemplary embodiment, as the resin particle dispersion, a toner having a structure including a continuous phase and a discontinuous phase having a core and a coating layer is preferably obtained by using the above composite resin particle dispersion and a resin particle dispersion for a continuous phase containing a binder resin (i).

[0235] Specifically, for example, an aggregating agent is added to the mixed dispersion, and the pH of the mixed dispersion is adjusted to be acidic (for example, pH 2 to 5). If necessary, a dispersion stabilizer is added. Then, the mixed dispersion is heated at a temperature close to the glass transition temperature of the resin particles (specifically, for example, within the range of the glass transition temperature of the resin particles of -30°C to -10°C) to aggregate the particles dispersed in the mixed dispersion, thereby forming aggregated particles.

[0236] In the aggregated particle formation step, for example, an aggregating agent can be added at room temperature (e.g., 25° C.) while stirring the mixed dispersion using a rotary shearing type homogenizer, the pH of the mixed dispersion can be adjusted to acidic (e.g., pH 2 to 5), a dispersion stabilizer can be added if necessary, and then heating can be performed.

[0237] Examples of aggregating agents include surfactants having opposite polarity to the surfactant as a dispersant to be added to the mixed dispersion, inorganic metal salts, divalent or multivalent metal complexes. In particular, when a metal complex is used as an aggregating agent, the amount of surfactant used is reduced and the charging performance is improved. If necessary, an additive that forms a complex or a similar bond with a metal ion can be used as an aggregating agent. A chelating agent is suitable for use as an additive.

[0238] Examples of the inorganic metal salt include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate, and inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide.

[0239] As the chelating agent, an aqueous chelating agent may be used. Examples of the chelating agent include oxycarboxylic acids such as tartaric acid, citric acid, and gluconic acid, iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), and ethylenediaminetetraacetic acid (EDTA).

[0240] The addition amount of the chelating agent is, for example, preferably in the range of 0.01 parts by weight to 5.0 parts by weight, and more preferably equal to or greater than 0.1 parts by weight and less than 3.0 parts by weight, relative to 100 parts by weight of the resin particles.

[0241] Coalescence step

[0242] Next, the aggregated particle dispersion in which the aggregated particles are dispersed is heated at a temperature equal to or higher than the glass transition temperature of the resin particles (eg, 10° C. to 30° C. higher than the glass transition temperature of the resin particles) to coalesce the aggregated particles and form toner particles.

[0243] Toner particles are obtained through the aforementioned steps.

[0244] Note that the toner particles can be obtained by the following steps: a step of obtaining an aggregated particle dispersion in which aggregated particles are dispersed, mixing the aggregated particle dispersion and a resin particle dispersion in which resin particles are dispersed, and aggregating the mixture to form second aggregated particles in a manner such that the resin particles are attached to the surfaces of the aggregated particles, and a step of forming toner particles having a core and shell structure by heating the second aggregated particle dispersion in which the second aggregated particles are dispersed and agglomerating the second aggregated particles.

[0245] Here, after the coalescence step is finished, the toner particles formed in the solution are subjected to a known washing step, a solid-liquid separation step, and a drying step, thereby obtaining dried toner particles.

[0246] In the washing step, from the viewpoint of charging characteristics, displacement washing using ion exchange water can be sufficiently performed. In addition, the solid-liquid separation step is not particularly limited, but from the viewpoint of productivity, suction filtration, pressure filtration, etc. are preferably performed. The method of the drying step is also not particularly limited, but from the viewpoint of productivity, freeze drying, airflow drying, fluidized drying, vibration type fluidized drying, etc. can be performed.

[0247] The toner according to the exemplary embodiment is produced, for example, by adding an external additive to the toner particles obtained in a dry state and mixing them. The mixing can be performed by using, for example, a V-type mixer, a Henschel mixer, a Loedige mixer, etc. In addition, if necessary, coarse particles of the toner can be removed by using a vibration sieving machine, a wind classifier, etc.

[0248] Electrostatic charge image developer

[0249] The electrostatic charge image developer according to the exemplary embodiment includes at least the toner according to the exemplary embodiment. The electrostatic charge image developer according to the exemplary embodiment may be a single-component developer including only the toner according to the exemplary embodiment, or may be a two-component developer in which the toner and the carrier are mixed with each other.

[0250] The carrier is not particularly limited, and a known carrier can be used. Examples of the carrier include: a coated carrier in which the surface of the core formed of magnetic particles is coated with a coating resin; a magnetic particle dispersed carrier in which the magnetic particles are dispersed and distributed in a matrix resin; and a resin impregnated carrier in which a resin is impregnated into porous magnetic particles.

[0251] Note that the magnetic particle dispersed carrier and the resin impregnated carrier may be carriers in which the forming particles of the foregoing carrier are provided as cores and the cores are coated with a coating resin.

[0252] Examples of magnetic particles include magnetic metals such as iron, nickel, and cobalt, and magnetic oxides such as ferrite and magnetite.

[0253] Examples of the coating resin and the base resin include polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymer, styrene-acrylate copolymer, a linear silicone resin formed by containing an organic siloxane bond or a modified product thereof, a fluororesin, a polyester, a polycarbonate, a phenolic resin, and an epoxy resin. The coating resin and the base resin may contain other additives such as conductive particles.

[0254] Examples of the conductive particles include metals such as gold, silver, and copper, and particles such as carbon black, titanium oxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, and potassium titanate.

[0255] Here, in order to coat the surface of the core with the coating resin, a method of coating the surface with a coating forming solution is used, in which the coating resin and various additives (if necessary) are dissolved in an appropriate solvent. The solvent is not particularly limited as long as the solvent is selected in consideration of the coating resin to be used and coating suitability.

[0256] Specific examples of the resin coating method include an immersion method in which the core is immersed in a coating-forming solution, a spraying method in which the coating-forming solution is sprayed onto the surface of the core, a fluidized bed method in which the coating-forming solution is sprayed onto the core in a state of being floated by fluid air, and a kneading coating method in which the core of the carrier is mixed with the coating-forming solution and the solvent is removed in a kneading coater.

[0257] The mixing ratio (mass ratio) of the toner and the carrier in the two-component developer is preferably toner:carrier=1:100 to 30:100, more preferably 3:100 to 20:100.

[0258] Image forming apparatus and image forming method

[0259] An image forming apparatus and an image forming method according to this exemplary embodiment will be described.

[0260] The image forming apparatus according to the exemplary embodiment is provided with: an image holding member; a charging unit that charges the surface of the image holding member; an electrostatic charge image forming unit that forms an electrostatic charge image on the charged surface of the image holding member; a developing unit that contains an electrostatic charge image developer and develops the electrostatic charge image formed on the surface of the image holding member into a toner image by using the electrostatic charge image developer; a transfer unit that transfers the toner image formed on the surface of the image holding member to the surface of a recording medium; and a fixing unit that fixes the toner image transferred to the surface of the recording medium. In addition, the electrostatic charge image developer according to the exemplary embodiment is used as the electrostatic charge image developer.

[0261] In an image forming device according to an exemplary embodiment, an image forming method (an image forming method according to an exemplary embodiment) includes the following steps: charging the surface of an image holding member; forming an electrostatic charge image on the charged surface of the image holding member; developing the electrostatic charge image formed on the surface of the image holding member into a colorant image using an electrostatic charge image developer according to an exemplary embodiment; transferring the colorant image formed on the surface of the image holding member onto the surface of a recording medium; and fixing the colorant image transferred to the surface of the recording medium.

[0262] As an image forming device according to an exemplary embodiment, a known image forming device such as includes: a direct transfer type device, which directly transfers the colorant image formed on the surface of the image holding member to a recording medium; an intermediate transfer type device, which primarily transfers the colorant image formed on the surface of the image holding member to the surface of the intermediate transfer body, and secondarily transfers the colorant image transferred to the surface of the intermediate transfer body to the surface of the recording medium; a device including a cleaning unit, which cleans the surface of the image holding member before charging and after the toner image is transferred; and a device including an erasing unit, which erases the charge by irradiating the surface of the image holding member with erasing light before charging and after the toner image is transferred.

[0263] In the case of using an intermediate transfer type device, the transfer unit is configured to include: an intermediate transfer body that transfers the colorant image onto a surface; a first transfer unit that primarily transfers the colorant image formed on the surface of the image holding member onto the surface of the intermediate transfer body; and a second transfer unit that secondarily transfers the colorant image formed on the surface of the intermediate transfer body onto the surface of the recording medium.

[0264] In the image forming apparatus according to the exemplary embodiment, for example, the unit including the developing unit may be a cartridge structure (processing cartridge) detachable from the image forming apparatus. As the processing cartridge, for example, a processing cartridge including a developing unit accommodating the electrostatic charge image developer according to the exemplary embodiment is preferably used.

[0265] Hereinafter, an example of an image forming apparatus according to an exemplary embodiment will be described. However, the process cartridge is not limited thereto. The main parts shown in the drawings will be described, but description of other parts will be omitted.

[0266] Figure 2 is a diagram showing a configuration of an image forming apparatus according to an exemplary embodiment.

[0267] like Figure 2The image forming apparatus shown is provided with an electrophotographic first image forming unit 10Y, a second image forming unit 10M, a third image forming unit 10C, and a fourth image forming unit 10K (image forming means), which output images of each color of yellow (Y), magenta (M), cyan (C), and black (K) based on color-separated image data. These image forming units (hereinafter referred to simply as "units" in some cases) 10Y, 10M, 10C, and 10K are arranged in parallel at a predetermined distance in the horizontal direction. Note that these units 10Y, 10M, 10C, and 10K may be process cartridges attached to and detached from the image forming apparatus.

[0268] On the upper side of each unit 10Y, 10M, 10C, and 10K in the figure, an intermediate transfer belt 20 as an intermediate transfer body extends through each unit. The intermediate transfer belt 20 is wound on a driving roller 22 and a supporting roller 24 that are in contact with the inner surface of the intermediate transfer belt 20, and travels in a direction toward the first unit 10Y to the fourth unit 10K, wherein the driving roller 22 and the supporting roller 24 are spaced apart from each other in the direction from left to right in the figure. A force is applied to the supporting roller 24 in a direction away from the driving roller 22 by a spring or the like (not shown), and tension is applied to the intermediate transfer belt 20 wound on the two rollers. An intermediate transfer body cleaning device 30 is provided on a side surface of the image holding member of the intermediate transfer belt 20 to face the driving roller 22.

[0269] In addition, toners including four color toners of yellow, magenta, cyan and black contained in toner boxes 8Y, 8M, 8C and 8K in developers (developing units) 4Y, 4M, 4C and 4K of the respective units 10Y, 10M, 10C and 10K are provided.

[0270] Since the first to fourth units 10Y, 10M, 10C, and 10K have the same configuration, here, the first unit 10Y for forming a yellow image disposed on the upstream side in the traveling direction of the intermediate transfer belt will be described as a representative. The same parts as those in the first unit 10Y are denoted by replacing the reference numerals of yellow (Y) with magenta (M), cyan (C), and black (K), and the description of the second unit 10M, the third unit 10C, and the fourth unit 10K will be omitted.

[0271] The first unit 10Y includes a photoreceptor 1Y serving as an image holding member. Arranged in order around the photoreceptor 1Y are: a charging roller (an example of a charging unit) 2Y that charges the surface of the photoreceptor 1Y to a predetermined potential; an exposure device (an example of an electrostatic charge image forming unit) 3 that forms an electrostatic charge image by exposing the charged surface with a laser beam 3Y based on a color separation image signal; a developer (an example of a developing unit) 4Y that develops the electrostatic charge image by supplying a charged toner to the electrostatic charge image; a first transfer roller 5Y (an example of a first transfer unit) that transfers the developed toner image onto the intermediate transfer belt 20; and a photoreceptor cleaning device (an example of a cleaning unit) 6Y that removes the toner remaining on the surface of the photoreceptor 1Y after the first transfer.

[0272] The first transfer roller 5Y is disposed on the inner side of the intermediate transfer belt 20 and is disposed at a position facing the photoreceptor 1Y. In addition, a bias power supply (not shown) for applying a first transfer bias is connected to each of the first transfer rollers 5Y, 5M, 5C, and 5K. Each bias power supply changes the transfer bias applied to each first transfer roller under the control of a control unit (not shown).

[0273] Hereinafter, an operation of forming a yellow image in the first unit 10Y will be described.

[0274] First, before the operation, the surface of the photoreceptor 1Y is charged to a potential of -600 V to -800 V by the charging roller 2Y.

[0275] By conducting (for example, the volume resistivity at 20°C is: 1×10 -6 The photoreceptor 1Y is formed by laminating a photosensitive layer on a substrate (Ωcm or less). The photosensitive layer generally has a high resistance (resistance of a general resin), but has a characteristic that when the laser beam 3Y is irradiated, the specific resistance of the portion irradiated by the laser beam changes. Therefore, according to the image data for yellow sent from the control unit (not shown), the laser beam 3Y is output to the surface of the charged photoreceptor 1Y through the exposure device 3. The laser beam 3Y is applied to the photosensitive layer on the surface of the photoreceptor 1Y, thereby forming an electrostatic charge image of a yellow image pattern on the surface of the photoreceptor 1Y.

[0276] The electrostatic charge image is an image formed on the surface of the photoreceptor 1Y by charging, and is a so-called negative latent image formed in the following manner: the resistivity of the irradiated portion of the photosensitive layer is reduced by the laser beam 3Y, and the charge charged on the surface of the photoreceptor 1Y flows, while the charge of the portion not irradiated by the laser beam 3Y remains.

[0277] The electrostatic charge image formed on the photoreceptor 1Y rotates to a predetermined developing position as the photoreceptor 1Y travels. Then, at the developing position, the electrostatic charge image on the photoreceptor 1Y is made visible as a toner image (developed image) by the developing device 4Y.

[0278] For example, in the developer 4Y, an electrostatic charge image developer containing at least a yellow toner and a carrier is accommodated. The yellow toner is frictionally charged by being stirred in the developer 4Y, and is held on a developer roller (an example of a developer holding body) with a charge of the same polarity (negative polarity) as the charge on the photoreceptor 1Y. Then, when the surface of the photoreceptor 1Y passes through the developer 4Y, the yellow toner is electrostatically attached to the discharged latent image portion on the surface of the photoreceptor 1Y, and the latent image is developed by the yellow toner. The photoreceptor 1Y on which the yellow toner image is formed then travels at a predetermined speed, and the toner image developed on the photoreceptor 1Y is conveyed to a predetermined first transfer position.

[0279] When the yellow toner image on the photoreceptor 1Y is conveyed to the first transfer position, the first transfer bias is applied to the first transfer roller 5Y, the electrostatic force from the photoreceptor 1Y toward the first transfer roller 5Y acts on the toner image, and the toner image on the photoreceptor 1Y is transferred onto the intermediate transfer belt 20. The transfer bias applied at this time is a (+) polarity opposite to the (-) polarity of the toner, and is controlled to +10 μA by a control unit (not shown) in the first unit 10Y, for example.

[0280] On the other hand, the toner remaining on the photoreceptor 1Y is removed and collected by the photoreceptor cleaning device 6Y.

[0281] Furthermore, the first transfer bias applied to the first transfer rollers 5M, 5C, and 5K after the second unit 10M is also controlled according to the first unit.

[0282] Thus, the intermediate transfer belt 20 to which the yellow toner image is transferred in the first unit 10Y is transported sequentially through the second unit 10M, the third unit 10C, and the fourth unit 10K, and the toner images of the respective colors are superimposed and transferred multiple times.

[0283] The intermediate transfer belt 20 on which the toner images of four colors are transferred multiple times through the first to fourth units leads to a second transfer section configured to include the intermediate transfer belt 20 and the support roller 24 in contact with the inner surface of the intermediate transfer belt, and a second transfer roller (an example of a second transfer device) 26 provided on the image holding surface side of the intermediate transfer belt 20. On the other hand, a recording paper (an example of a recording medium) P is fed to a gap in which the second transfer roller 26 and the intermediate transfer belt 20 are in contact with each other via a feeding mechanism at a predetermined timing, and a second transfer bias is applied to the support roller 24. The transfer bias applied at this time is the same as the polarity (-) of the toner, and an electrostatic force from the intermediate transfer belt 20 to the recording paper P acts on the toner image, so that the toner image is transferred to the recording paper P on the intermediate transfer belt 20. The second transfer bias at this time is determined based on the resistance detected by a resistance detection unit (not shown) that detects the resistance of the second transfer section, and is voltage-controlled.

[0284] Thereafter, the recording paper P is sent to a pressure contact portion (nip portion) of a pair of fixing rollers in a fixing device (example fixing unit) 28 , the toner image is fixed on the recording paper P, and a fixed image is formed.

[0285] Examples of the recording paper P to which the toner image is transferred include plain paper used in electrophotographic copiers, printers, and the like. As the recording medium, in addition to the recording paper P, OHP paper and the like can be exemplified. In order to further improve the smoothness of the image surface after fixing, the surface of the recording paper P is also preferably smooth, and for example, coated paper in which the surface of plain paper is coated with a resin or the like and art paper for printing are preferably used.

[0286] The recording paper P on which the color image fixing is completed is transported to the discharge portion, and a series of color image forming operations are completed.

[0287] Process cartridges and toner cartridges

[0288] A process cartridge according to an exemplary embodiment will be described. The process cartridge according to the exemplary embodiment is provided with a developing unit that accommodates an electrostatic charge image developer according to the exemplary embodiment, develops an electrostatic charge image formed on the surface of an image holding member into a toner image with the electrostatic charge image developer, and is detachable from an image forming apparatus.

[0289] The process cartridge according to the exemplary embodiment is not limited to the above-described configuration, and may be configured to include a developer and at least one selected from other units such as an image holding member, a charging unit, an electrostatic charge image forming unit, and a transfer unit.

[0290] Hereinafter, an example of a process cartridge according to this exemplary embodiment will be described. However, the process cartridge is not limited thereto. The main parts shown in the drawings will be described, but description of other parts will be omitted.

[0291] Figure 3 is a configuration diagram illustrating an example of a process cartridge according to this exemplary embodiment.

[0292] Figure 3 The processing box 200 shown is configured so that the photosensitive body 107 (an example of an image holding member), a charging roller 108 (an example of a charging unit) arranged near the photosensitive body 107, a developer 111 (an example of a developing unit), and a photosensitive body cleaning device 113 (an example of a cleaning unit) are integrally combined and held by a housing 117, and the housing 117 is provided with an attachment rail 116 and an opening portion 118 for exposure.

[0293] Note that Figure 3 , reference numeral 109 denotes an exposure device (an example of an electrostatic charge image forming unit), reference numeral 112 denotes a transfer device (an example of a transfer unit), reference numeral 115 denotes a fixing device (an example of a fixing unit), and reference numeral 300 denotes a recording paper (an example of a recording medium).

[0294] Next, a toner cartridge according to the exemplary embodiment will be described.

[0295] The toner cartridge according to the exemplary embodiment accommodates the toner according to the exemplary embodiment and is detachable from the image forming apparatus. The toner cartridge accommodates the toner for replenishment supplied to the developing unit provided in the image forming apparatus.

[0296] like Figure 2 The image forming apparatus shown has a configuration in which toner cartridges 8Y, 8M, 8C, and 8K are detachable from the apparatus, and developers 4Y, 4M, 4C, and 4K are connected to toner cartridges corresponding to the respective developers (colors) through toner supply pipes (not shown), respectively. In addition, in the case where the toner contained in the toner cartridge is low in flow, the toner cartridge is replaced.

[0297] Example

[0298] Hereinafter, the present invention will be described more specifically through embodiments, but the present invention is not limited to the following embodiments as long as it does not exceed the gist thereof. In the following description, all "parts" and "%" are based on mass unless otherwise specified.

[0299] Synthesis of Crystalline Polyester Resin 1

[0300] 225 parts of 1,10-dodecane diacid, 174 parts of 1,10-decanediol and 0.8 parts of dibutyltin oxide as a catalyst were placed in a heat-dried three-necked flask. After that, the air in the three-necked flask was replaced with nitrogen under reduced pressure operation and made into an inert atmosphere, and the mixture was stirred at 180°C for 5 hours by mechanical stirring and refluxed to promote the reaction. During the reaction, the water produced in the reaction system was distilled off. Then, under reduced pressure, the temperature was gradually increased to 230°C, and the mixture was stirred for 2 hours. When it became viscous, the molecular weight was checked by GPC, and when the weight average molecular weight reached 17500, the vacuum distillation was stopped to obtain a crystalline polyester resin 1.

[0301] Synthesis of Amorphous Polyester Resin 1

[0302] Bisphenol A propylene oxide adduct: 367 parts

[0303] Bisphenol A ethylene oxide adduct: 230 parts

[0304] Terephthalic acid: 163 parts

[0305] ·Trimellitic anhydride: 20 parts

[0306] Dibutyltin oxide: 4 parts

[0307] After the above components were placed in a heat-dried three-necked flask, the air in the container was decompressed by a decompression operation to form another inert atmosphere with nitrogen, and the reaction was carried out at 230° C. and normal pressure (101.3 kPa) by mechanical stirring for 10 hours, and further reacted at 8 kPa for 1 hour. The mixture was cooled to 210° C., 4 parts of trimellitic anhydride were added thereto, reacted for 1 hour, and reacted at 8 kPa until the softening temperature reached 118° C., thereby obtaining an amorphous polyester resin 1.

[0308] The softening temperature of the resin was set to a temperature at which, while heating the sample at a heating rate of 6° C. / min by using a flow tester (CFT-5000 produced by Shimadzu Corporation), a load of 1.96 MPa was applied to 1 g of the sample with a plunger, and then the sample was extruded from a nozzle having a diameter of 1 mm and a length of 1 mm so that half of the sample flowed out.

[0309] Synthesis of Amorphous Polyester Resin 2

[0310] Bisphenol A propylene oxide adduct: 469 parts

[0311] Bisphenol A ethylene oxide adduct: 137 parts

[0312] Terephthalic acid: 152 parts

[0313] Fumaric acid: 20 parts

[0314] Dibutyltin oxide: 4 parts

[0315] After the above components were placed in a heat-dried three-necked flask, the air in the container was decompressed by a decompression operation to form another inert atmosphere with nitrogen, and the reaction was carried out at 230° C. and normal pressure (101.3 kPa) by mechanical stirring for 10 hours, and further reacted at 8 kPa for 1 hour. The reaction mixture was cooled to 210° C., 4 parts of trimellitic anhydride were added, reacted for 1 hour, and reacted at 8 kPa until the softening temperature reached 107° C., thereby obtaining an amorphous polyester resin 2.

[0316] The difference in SP value between the amorphous polyester resin 1 and the amorphous polyester resin 2 calculated by the above method was 0.14.

[0317] Production of Crystalline Polyester Resin Particle Dispersion Liquid 1

[0318] 100 parts of crystalline polyester resin 1, 40 parts of methyl ethyl ketone and 30 parts of isopropanol were placed in a separable flask, fully mixed and dissolved at 75°C, and 6.0 parts of 10% ammonia solution were added dropwise to the mixture. The heating temperature was lowered to 60°C, and ion exchange water was added dropwise at a feed rate of 6 g / min using a feed pump while stirring, and the solution became uniformly turbid, and then the feed rate was increased to 25 g / min. When the volume of the solution reached 400 parts, the addition of ion exchange water was stopped. Then, the solvent was removed under reduced pressure to obtain a crystalline polyester resin particle dispersion 1. The volume average particle diameter of the obtained crystalline polyester resin particle dispersion 1 was 168 nm, and the solid concentration was 11.5%.

[0319] Production of amorphous polyester resin particle dispersion 1

[0320] Amorphous polyester resin 1: 300 parts

[0321] Methyl ethyl ketone: 218 parts

[0322] Isopropyl alcohol: 60 parts

[0323] 10% ammonia solution: 10.6 parts

[0324] The above components (after removing insolubles with respect to the amorphous polyester resin) were placed in a separable flask, mixed and dissolved, and then ion exchange water was added dropwise at a feed rate of 8 g / min by a feed pump while heating and stirring the mixture at 40°C. After the solution became turbid, the liquid delivery rate was increased to 12 g / min to cause phase inversion, and when the liquid delivery amount reached 1050 parts, the dropwise addition was stopped. Then, the solvent was removed under reduced pressure to obtain an amorphous polyester resin particle dispersion 1. The volume average particle diameter of the amorphous polyester resin particle dispersion 1 was 168 nm, and the solid concentration was 30%.

[0325] Production of amorphous polyester resin particle dispersion 2

[0326] Amorphous polyester resin 2: 300 parts

[0327] Methyl ethyl ketone: 200 parts

[0328] Isopropyl alcohol: 50 parts

[0329] 10% ammonia solution: 10.6 parts

[0330] The above components (after removing insolubles with respect to the amorphous polyester resin) were placed in a separable flask, mixed and dissolved, and then ion exchange water was added dropwise at a feed rate of 8 g / min by a feed pump while heating and stirring the mixture at 40°C. After the solution became turbid, the liquid delivery rate was increased to 12 g / min to cause phase inversion, and when the liquid delivery amount reached 1050 parts, the dropwise addition was stopped. Thereafter, the solvent was removed under reduced pressure to obtain amorphous polyester resin particle dispersion 2. The volume average particle diameter of the amorphous polyester resin particle dispersion 2 was 160 nm, and the solid concentration was 30%.

[0331] Production of amorphous polyester resin particle dispersion 3

[0332] Amorphous polyester resin particle dispersion 3 was obtained in the same manner except that the content of methyl ethyl ketone in amorphous polyester resin particle dispersion 2 was changed to 300 parts. Amorphous polyester resin particle dispersion 3 had a volume average particle diameter of 100 nm and a solid concentration of 30%.

[0333] Production of amorphous polyester resin particle dispersion 4

[0334] Amorphous polyester resin particle dispersion 4 was obtained in the same manner except that the content of methyl ethyl ketone in amorphous polyester resin particle dispersion 2 was changed to 130 parts. Amorphous polyester resin particle dispersion 4 had a volume average particle diameter of 250 nm and a solid concentration of 30%.

[0335] Production of amorphous polyester resin particle dispersion 5

[0336] Amorphous polyester resin particle dispersion 5 was obtained in the same manner except that the content of methyl ethyl ketone was changed to 150 parts in amorphous polyester resin particle dispersion 5. Amorphous polyester resin particle dispersion 5 had a volume average particle diameter of 200 nm and a solid concentration of 30%.

[0337] Vinyl / amorphous polyester composite resin particle dispersion 1

[0338] 160 parts of amorphous polyester resin particle dispersion 2, 253 parts of ion exchange water, 96 parts of butyl acrylate and 3.6 parts of 10% ammonia solution were put into a 2L cylindrical stainless steel container, and dispersed and mixed for 10 minutes by setting the number of revolutions of a homogenizer (Ultra-Turrax T50, manufactured by IKA Co., Ltd.) to 10000 rpm. After that, the raw material dispersion was transported to a polymerization kettle equipped with a thermometer and a stirring device using a double-paddle stirring blade to form a laminar flow, and heating was started with a hooded heater under a nitrogen atmosphere by setting the number of revolutions of stirring to 200 rpm, and the mixture was kept at 75°C for 30 minutes. Thereafter, a mixed solution of 1.8 parts of potassium persulfate (KPS) and 120 parts of ion exchange water was added dropwise by a liquid feed pump over 120 minutes, and then kept at 75°C for 210 minutes. After the liquid temperature was lowered to 50°C, 5.4 parts of anionic surfactant (NeogenRK, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) was added to obtain vinyl / amorphous polyester composite resin particle dispersion 1. The volume average particle diameter of vinyl / amorphous polyester composite resin particle dispersion 1 was 220 nm, and the solid concentration was 32%.

[0339] Vinyl / amorphous polyester composite resin particle dispersion 2

[0340] A vinyl / amorphous polyester composite resin particle dispersion 2 was obtained in the same manner except that the amorphous polyester resin particle dispersion 2 was changed to the amorphous polyester resin particle dispersion 3 and the content of butyl acrylate in the vinyl / amorphous polyester composite resin particle dispersion 1 was changed to 132 parts. The volume average particle diameter of the vinyl / amorphous polyester composite resin particle dispersion 2 was 130 nm and the solid concentration was 32%.

[0341] Vinyl / amorphous polyester composite resin particle dispersion 3

[0342] Vinyl / amorphous polyester composite resin particle dispersion 3 was obtained in the same manner except that amorphous polyester resin particle dispersion 2 was changed to amorphous polyester resin particle dispersion 4 and the content of butyl acrylate in vinyl / amorphous polyester composite resin particle dispersion 1 was changed to 72 parts. The volume average particle diameter of vinyl / amorphous polyester composite resin particle dispersion 3 was 320 nm and the solid concentration was 32%.

[0343] Vinyl / amorphous polyester composite resin particle dispersion 4

[0344] Vinyl / amorphous polyester composite resin particle dispersion 4 was obtained in the same manner except that amorphous polyester resin particle dispersion 2 was changed to amorphous polyester resin particle dispersion 5 and the content of butyl acrylate in vinyl / amorphous polyester composite resin particle dispersion 1 was changed to 72 parts. The volume average particle diameter of vinyl / amorphous polyester composite resin particle dispersion 4 was 220 nm, and the solid concentration was 32%.

[0345] Vinyl / amorphous polyester composite resin particle dispersion 5

[0346] Vinyl / amorphous polyester composite resin particle dispersion 5 was obtained in the same manner except that the content of butyl acrylate in vinyl / amorphous polyester composite resin particle dispersion 1 was changed to 132 parts. Vinyl / amorphous polyester composite resin particle dispersion 5 had a volume average particle diameter of 220 nm and a solid concentration of 32%.

[0347] Vinyl / amorphous polyester composite resin particle dispersion 6

[0348] Vinyl / amorphous polyester composite resin particle dispersion 6 was obtained in the same manner except that amorphous polyester resin particle dispersion 2 was changed to amorphous polyester resin particle dispersion 3 and the content of butyl acrylate in vinyl / amorphous polyester composite resin particle dispersion 1 was changed to 102 parts. The volume average particle diameter of vinyl / amorphous polyester composite resin particle dispersion 6 was 140 nm and the solid concentration was 32%.

[0349] Vinyl / amorphous polyester composite resin particle dispersion 7

[0350] Vinyl / amorphous polyester composite resin particle dispersion 7 was obtained in the same manner except that amorphous polyester resin particle dispersion 2 was changed to amorphous polyester resin particle dispersion 4 and the content of butyl acrylate in vinyl / amorphous polyester composite resin particle dispersion 1 was changed to 36 parts. The volume average particle diameter of vinyl / amorphous polyester composite resin particle dispersion 7 was 300 nm and the solid concentration was 32%.

[0351] Vinyl / amorphous polyester composite resin particle dispersion 8

[0352] Vinyl / amorphous polyester composite resin particle dispersion 8 was obtained in the same manner except that the content of butyl acrylate in vinyl / amorphous polyester composite resin particle dispersion 1 was changed to 72 parts. Vinyl / amorphous polyester composite resin particle dispersion 8 had a volume average particle diameter of 190 nm and a solid concentration of 32%.

[0353] Vinyl / amorphous polyester composite resin particle dispersion 9

[0354] Vinyl / amorphous polyester composite resin particle dispersion 9 was obtained in the same manner except that amorphous polyester resin particle dispersion 2 was changed to amorphous polyester resin particle dispersion 5 and the content of butyl acrylate in vinyl / amorphous polyester composite resin particle dispersion 1 was changed to 132 parts. The volume average particle diameter of vinyl / amorphous polyester composite resin particle dispersion 9 was 260 nm, and the solid concentration was 32%.

[0355] In the vinyl / amorphous polyester composite resin particle dispersions 1 to 9, the glass transition temperature Tg of the vinyl resin constituting the coating layer is lower than the temperature (110° C.) of a fixing device at the time of <Image Forming> (described later).

[0356] Production of release agent dispersion 1

[0357] Paraffin wax (HNP9, manufactured by Nippon Seiro Co., Ltd.): 500 parts

[0358] Anionic surfactant (NEOGEN RK, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.): 50 parts

[0359] Ion exchange water: 1700 parts

[0360] The above materials were mixed with each other, the mixture was heated at 110° C., dispersed by using a homogenizer (Ultra-Turrax T50, manufactured by IKA Ltd.), and then subjected to dispersion treatment by using a Manton-Gaulin high-pressure homogenizer (manufactured by Manton Gaulin Mfg Company Inc.), thereby generating a release agent dispersion 1 (solid content concentration: 32 wt %) in which a release agent having an average particle size of 180 nm was dispersed.

[0361] Production of cyan pigment dispersion

[0362] Pigment Blue 15:3 (manufactured by DIC): 200 parts

[0363] Anionic surfactant (NEOGEN R, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.): 1.5 parts

[0364] Ion exchange water: 800 parts

[0365] The above components were mixed and dispersed by using a disperser Cavitron (manufactured by Tahiyo Kiko Co., Ltd., CR1010) for about 1 hour to obtain a cyan pigment dispersion liquid (solid content concentration: 20% by weight).

[0366] Production of cyan toner 1

[0367] Amorphous polyester resin particle dispersion 1: (amount shown in Table 1)

[0368] · Vinyl / amorphous polyester composite resin particle dispersion 1: (amount shown in Table 1)

[0369] Crystalline polyester resin particle dispersion 1: (amount shown in Table 1)

[0370] Release agent dispersion 1: 45 parts

[0371] Cyan pigment dispersion: 90 parts

[0372] Nonionic surfactant (IGEPALCA897): 1.40 parts

[0373] The above raw materials were placed in a 2L cylindrical stainless steel container, dispersed and mixed for 10 minutes while applying shear force at 4000 rpm with a homogenizer (Ultra-Turrax T50, manufactured by IKA Co., Ltd.). Then, 1.75 parts of a 10% nitric acid aqueous solution of polyaluminum chloride was gradually added dropwise as a flocculant, and the mixture was dispersed for 15 minutes and mixed by setting the number of revolutions of the homogenizer to 5000 rpm to obtain a raw material dispersion.

[0374] After that, the raw material dispersion was transferred to a polymerization kettle equipped with a thermometer and a stirring device using a double-paddle stirring blade to form a laminar flow, and heating was started with a hooded heater by setting the stirring rotation number to 550 rpm, and the mixture was maintained at 49°C to promote the growth of aggregated particles. At this time, the pH of the raw material dispersion was controlled within the range of 2.2 to 3.5 with 0.3N nitric acid or 1N sodium hydroxide aqueous solution. The mixture was maintained within the above pH range for about 2 hours to form aggregated particles.

[0375] Next, 184 parts of amorphous polyester resin particle dispersion 1 were added to attach the resin particles of the binder resin to the surface of the aggregated particles. The temperature was further raised to 53°C, and the aggregated particles were arranged while checking the particle size and morphology with an optical microscope and Multisizer II. After that, the pH was adjusted to 7.8 with a 5% sodium hydroxide aqueous solution and maintained for 15 minutes. Thereafter, the pH was raised to 8.0 to melt the aggregated particles, and then the temperature was raised to 85°C. After checking that the aggregated particles were melted with an optical microscope, heating was stopped after 2 hours, and cooling was performed at a temperature drop rate of 1.0°C / min. Then, the resultant was sieved with a 20μm sieve, repeatedly washed with water, and then dried with a vacuum dryer to obtain cyan toner particles 1.

[0376] Note that, for the obtained cyan toner particles 1, “the presence or absence of a continuous phase and a discontinuous phase having a core and a coating layer,” “the area occupied by the discontinuous phase relative to the cross-sectional area of ​​the toner [%],” “the average equivalent circle diameter L1 [nm] of the discontinuous phase,” “the average thickness L2 [nm] of the coating layer,” “L2 / L1,” “the weight ratio C / A1 of the crystalline polyester resin 1 (C) to the amorphous polyester resin 1 (A1) contained in the continuous phase,” and “when a boundary line having the same shape as that of the cross-sectional area of ​​the toner and surrounding an area of ​​50% of the cross-sectional area of ​​the toner is coaxially drawn on the cross-sectional area of ​​the toner, the ratio a1 / a2 of the area a1 of the discontinuous phase existing within the boundary line to the area a2 of the discontinuous phase existing outside the boundary line” were determined or measured by the above-mentioned method. The results are shown in Table 1.

[0377] 0.5% of hexamethyldisilazane-treated silica having an average particle size of 40 nm and 0.7% of a titanium compound having an average particle size of 30 nm (obtained by baking in a weight ratio relative to the toner particles in each case after being treated with 50% of isobutyltrimethoxysilane in metatitanic acid) were added as external additives to the obtained cyan toner particles 1, and the resultant was mixed with a 75 L Henschel mixer for 10 minutes, after which the mixture was sieved by an air sieve sieving machine Hi-Bolter 300 (manufactured by Shin-Tokyo Machine Company) to produce cyan toner 1. The volume average particle diameter of the obtained cyan toner 1 was 5.8 μm.

[0378] Production of cyan developer 1

[0379] Next, for 100 parts of the ferrite core having an average particle size of 35 μm, 0.15 parts of vinylidene fluoride and 1.35 parts of a copolymer of methyl methacrylate and trifluoroethylene resin (polymerization ratio of 80:20) were applied using a kneader to produce a carrier. The obtained carrier and cyan toner 1 were mixed in a 2-liter V-type blender at a ratio of 100 parts:8 parts, respectively, to produce cyan developer 1.

[0380] Production of cyan toners 2 to 19 and cyan developers 2 to 19

[0381] Cyan toners 2 to 19 and cyan developers 2 to 19 were produced in the same manner as Cyan toner 1 and Cyan developer 1, except that the type and addition amount of the dispersion liquid used were changed as shown in Table 1.

[0382]

[0383] Imaging

[0384] A PREMAGE 355 fixing unit manufactured by Toshiba Tec Corporation was removed, its coil spring was replaced, the load for pressing the heating belt and the pressure roller was adjusted to 31 kgf, and wiring for supplying power to the fixing unit was provided to use as a fixing test unit (fixing device).

[0385] On the other hand, in order to obtain an unfixed toner image, a DCIIC 7500 fixing unit manufactured by Fuji Xerox Co., Ltd. was removed and modified so that the copy was discharged in an unfixed state. As an evaluation chart, an entire surface solid image adjusted so that the toner loading amount was 10.0 g / cm2 was used. The unfixed toner image was produced in an environment of a temperature of 25° C. and a humidity of 90%.

[0386] In addition, a fixing test unit was installed so that the produced unfixed toner image flowed into the fixing test unit, 500 images were continuously printed, and the presence or absence of image defects on the 50th and 500th sheets of paper was evaluated, and the scratch strength was evaluated. The area of ​​the image on the paper was 30%, the temperature of the fixing device was 110° C., 150° C., and 200° C., and SP paper and OS coated 127 gsm paper (both manufactured by Fuji Xerox Co., Ltd.) were used.

[0387] Evaluation method for image defects (durability, hot offset resistance).

[0388] The case where at least one of a missing image, a rough image, and a scratched image is observed when visually observing the fixed image is defined as “visible”, the case where at least one of a missing image, a rough image, and a scratched image is slightly observed is defined as “slightly visible”, the case where at least one of a missing image, a rough image, and a scratched image is very slightly observed is defined as “very slight”, and the case where no missing image, a rough image, and a scratched image are observed is defined as “not visible”.

[0389] The evaluation results are shown in Table 2.

[0390] G0: The defect appears in the entire image (cold offset occurs)

[0391] G1: At least one of missing image, rough image, and scratched image is observed

[0392] G2: At least one of missing image, rough image, and scratched image is slightly observed

[0393] G3: Image roughness was very slightly observed, but no problem in actual use

[0394] G4: Missing images, rough images, and scratched images were not observed.

[0395] Scratch image strength evaluation method

[0396] The scratched image strength was evaluated under a pressure of 0.5 kg using a scratch hardness tester Model 318 manufactured by ERICHSEN GMBH & CO., KG.

[0397] The evaluation is as follows and the evaluation results are shown in Table 3.

[0398] A: The density (muscle in the image) has hardly decreased

[0399] B: A decrease in density occurs (muscles in the image), but the image is not peeled off.

[0400] C: A portion of the image is peeled off.

[0401] D: The image defect is serious and unacceptable

[0402] The above description of exemplary embodiments of the present invention has been provided for the purpose of illustration and description. It is not intended to be exhaustive or to limit the present invention to the precise form disclosed. Obviously, many modifications and variations will be apparent to those skilled in the art. These embodiments are selected and described in order to best explain the principles of the present invention and its practical application, so that other technical personnel in the art can understand the various embodiments of the present invention and the various modifications suitable for the intended specific use. The scope of the present invention is defined by the appended claims and their equivalents.

[0403]

[0404]

Claims

1. An electrostatic charge image developing toner, the electrostatic charge image developing toner comprising: a continuous phase comprising a binder resin (i); as well as a discontinuous phase having a core comprising a binder resin (ii) and a coating layer covering the core and comprising a binder resin (iii), and being dispersed in the continuous phase, Herein, the continuous phase comprises an amorphous polyester resin A1 and a crystalline polyester resin C as the binder resin (i), the core comprises an amorphous polyester resin A2 as the binder resin (ii), and the coating comprises a vinyl resin B as the binder resin (iii).

2. The electrostatic charge image developing toner according to claim 1, in, In a cross section of the toner, a ratio of an area occupied by the discontinuous phase to a cross-sectional area of ​​the toner is 5% to 15%.

3. The electrostatic charge image developing toner according to claim 1, in, The discontinuous phase has an average equivalent circle diameter of 100 nm to 300 nm.

4. The electrostatic charge image developing toner according to claim 1, in, The coating has an average thickness of 25 nm to 50 nm.

5. The electrostatic charge image developing toner according to claim 1, in, A ratio L2 / L1 of an average thickness L2 of the coating layer to an average equivalent circle diameter L1 of the discontinuous phase is 0.12 to 0.

25.

6. The electrostatic charge image developing toner according to claim 1, in, The binder resin (iii) contained in the coating layer has a different structure from a constituent unit in a polymer chain relative to the binder resin (i) contained in the continuous phase and the binder resin (ii) contained in the core.

7. The electrostatic charge image developing toner according to claim 1, in, The binder resin (iii) contained in the coating layer forms a chemical bond with respect to the binder resin (ii) contained in the core at an interface between the core and the coating layer.

8. The electrostatic charge image developing toner according to claim 1, in, A weight ratio C / A1 of the crystalline polyester resin C contained in the continuous phase to the amorphous polyester resin A1 contained in the continuous phase is 0.12 to 0.

40.

9. The electrostatic charge image developing toner according to claim 1, in, The difference in SP value between the amorphous polyester resin A1 and the amorphous polyester resin A2 is 0.20 or less.

10. The electrostatic charge image developing toner according to claim 1, in, Both the amorphous polyester resin A1 and the amorphous polyester resin A2 have a total of 50% by weight or more of at least one of a structure derived from a bisphenol A propylene oxide adduct and a structure derived from a bisphenol A ethylene oxide adduct.

11. The electrostatic charge image developing toner according to claim 1, in, In the cross-section of the colorant, when a boundary line having the same shape as that of the cross-section of the colorant and enclosing an area of ​​50% of the cross-sectional area of ​​the colorant is coaxially drawn on the cross-section of the colorant, a ratio a1 / a2 of an area a1 of the discontinuous phase existing within the boundary line to an area a2 of the discontinuous phase existing outside the boundary line is 0.8 to 1.

2. 12 . An electrostatic charge image developer comprising the electrostatic charge image developing toner according to claim 1 .

13. A toner cartridge configured to accommodate the electrostatic charge image developing toner according to claim 1, in, The toner cartridge is detachable from the image forming apparatus.

Citation Information

Patent Citations

  • Toner

    JP2014006339A

  • Toner and developer

    JP2016114782A

  • Toner

    JP2017198980A

  • Toner, developing device, and image forming apparatus

    JP2018010286A

  • Toner for electrostatic latent image development

    JP2017203850A